Conceptualizing the peer contribution in Open Dialogue practice - Hendy, Corrine; Tew, Jerry; Carr, Sarah (Frontiers in Psychology, 2023)
In English mental health services, people with their own experience of mental distress have trained as Open Dialogue practitioners and have been employed as peer practitioners, co-working as equals alongside workers with professional backgrounds in Network Meetings. The conceptual underpinnings of the peer practitioner role have been drawn from the principles and relational approach of Intentional Peer Support. These have significant similarities with Open Dialogue, in terms of philosophical and theoretical orientations, with a particular focus on what happens in the 'between' of a relational encounter. However, there are also significant differences in how practice principles are conceptualized, particularly around areas such as mutuality and selfdisclosure. This article offers an analysis of this conceptual territory drawing on the relevant literature. This is then taken forward with the teasing out of specific practice principles that capture the unique contribution that peer practitioners can bring to Open Dialogue practice. These are derived through discussions that took place in an Action Learning Set for peer practitioners who have been involved in delivering Open Dialogue services in mainstream mental health service settings. This was part of a wider research study entitled Open Dialogue: Development and Evaluation of a Social Network Intervention for Severe Mental Illness (ODDESSI). The principles address how peer practitioners may be particularly well-placed to offer attunement, validation, connection and mutuality, and self-disclosure -and hence how they may be able to contribute an additional dimension to dialogical practice.